British masculinity in the "Gentleman's magazine," 1731 to 1815 - Williamson, Gillian (Genders and sexualities in history., 2016)
"Launched in 1731, the monthly Gentleman's Magazine was the dominant periodical of the eighteenth century, drawing its large readership from across the literate population of Great Britain and the English-speaking world. Its readers were highly responsive. By the 1740s their letters, poems and family announcements, especially obituaries, filled at least half its pages, sitting alongside articles by a circle that included Samuel Johnson. It was a Georgian social network as readers engaged in a continuous dialogue with each other, but not all these readers were as comfortably established as gentlemen as the title implied. This study traces how, from launch to the Battle of Waterloo in 1815, the magazine developed as a vehicle for the creation and national dissemination of a new middling-sort masculine gentlemanliness in a Britain that was increasingly commercial, fluid and open. It was an accessible gentlemanliness based on an ideology of merit through occupational success allied to personal probity. From the close of the Seven Year's War in 1763 the magazine used the merit of the self-made man to challenge the aristocratic ruling class. It was therefore a major contributor to the development of Victorian middle-class identity. Indeed, the meritorious self-made man remains one of the bulwarks of Conservative thought today"--